Neutron production measurement in the 125 mA 5 MeV deuteron beam commissioning of Linear IFMIF Prototype Accelerator (LIPAc) RFQ. (23rd September 2021) - Kondo, Keitaro; Kwon, Saerom; Kumagai, Kohki; Akagi, Tomoya; Bellan, Luca; Cara, Philippe; Carin, Yann; Comunian, Michele; Dzitko, Herve; Fagotti, Enrico; Gex, Dominique; Grespan, Francesco; et al.
Abstract: The validation of the Linear IFMIF Prototype Accelerator (LIPAc) is being conducted in Rokkasho Fusion Institute of QST, Aomori, Japan. The beam commissioning of the novel LIPAc RFQ has been progressing significantly, and the acceleration of the world highest current deuteron beam of 125 mA to 5 MeV (1 ms, 1 Hz pulsed beam) was achieved for the 1st time in July 2019. This study is devoted to evaluating the amount of beam loss during the high current acceleration phase by measuring the neutron produced by the interaction of the beam with accelerator components so as to verify the accelerator design. The foil activation method and the 3 He neutron probes were utilized. It turned out that there was no significant trace of unexpected beam loss at the high energy section of the RFQ and the medium energy beam transport (MEBT) section. The measurement using the 3 He neutron probes provided an evidence that the beam loss was well controlled in the RFQ cavity as designed. This study concludes that the LIPAc RFQ as well as MEBT is working well as predicted by the design calculation, and its concept is successful.